CSR analysis of plant functional types in highly diverse tropical grasslands of harsh environments - Negreiros, Daniel; Le Stradic, Soizig; Fernandes, G. Wilson; Rennó, Henrique C (Plant ecology, 2014)
The classification of plant species according to the CSR ecological strategy scheme has been proposed as a common language that allows comparison among species, communities, and floras. Although several studies on European continent have demonstrated a consistent association between CSR strategies and key ecosystem processes, studies of this type are still lacking in other ecoregions worldwide. For the first time, the CSR strategy scheme is applied in a tropical plant community. In a Brazilian mountain grassland ecosystem characterized by both high biodiversity and environmental stress, we sampled various functional traits of 48 herbaceous species in stony and sandy grasslands, and evaluated the relationship between CSR strategies and functional traits with several environmental parameters. The extremely infertile soils in the two studied habitats may have acted as a major environmental filter leading to a clear predominance of the stress-tolerant strategy in both communities. However, fine-scale environmental differences between the two communities resulted in the filtering of distinct functional trait values. The sites with coarser soil texture, lower percentage of plant cover and (paradoxically) higher mineral nutrient concentrations favored plants with narrower leaves, higher stress tolerance, lower competitiveness, and higher sclerophylly (i.e., lower specific leaf area and higher leaf dry matter content). The comparison between the functional character of stony and sandy communities evidenced the influence of soil texture and water availability in the environmental filtering. This study highlighted the validity of the CSR classification outside the temperate region where it was originally developed and corroborated.